Occurrence of Drosophila suzukii (Matsumura, 1931) (Diptera, Drosophilidae) in vineyard cultivars in the Serra Gaúcha Region, Brazil - Foppa, Fabiane; Borba, Regina da Silva (Scientia Agraria Paranaensis, 2023)
In Rio Grande do Sul State, viticulture is an activity of great importance. Drosophila suzukii (Matsumura, 1931) (Diptera, Drosophilidae) is a polyphagous pest with a small body size that lays its eggs in healthy, intact fruits. This study monitors D. suzukii in different grapevine cultivars and in the grape receiving area of ​​a winery, verifying berries infestation, as well as the pest’s body size. The monitoring of D. suzukii adults was carried out by installing a fly trap containing apple cider vinegar as a food attractant in each area of ​​the vineyard and in the winery. The insects collected were identified based on their external morphology and genitalia analysis. Four hundred berries were randomly collected in each area and placed in jars until all adults emerged, after which they were identified and sexed. Females were measured using a digital caliper. The Moscato Bailey cultivar had the highest number of emerged D. suzukii adults. Females from the Moscato Bailey and Malvasia cultivars had larger body sizes. During the monitoring period, the presence of adults D. suzukii was observed in grapevines of the Malvasia, Merlot, Tannat, Moscato Bailey, and Riesling cultivars in the municipality of Farroupilha, as well as in the grape receiving area.